Analisis Normatif Asas Itikad Baik dalam Mediasi Elektronik Sengketa Perdata - Absi, Warmiyana Zairi; Candra, Andi (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2026)
Advances in information technology are driving the transformation of judicial services in Indonesia through the e-Court system, with the aim of realizing the principles of simple, swift, and affordable justice. In this context, mediation as a mandatory procedure for civil disputes has also been digitized through electronic mediation, namely a technology-based mediation process without the physical presence of the parties. Although it offers efficiency in terms of time, cost, and access to justice, the effectiveness of electronic mediation depends on the application of the principle of good faith. This study aims to conduct a normative analysis of the regulation and enforcement of this principle within Indonesia’s e-Court system. The methodology employed is normative legal research using a regulatory, conceptual, and analytical approach, through an examination of regulations governing mediation and electronic court proceedings. The analysis reveals that while a legal foundation for electronic mediation exists, the regulations do not yet fully incorporate operational indicators and robust enforcement mechanisms regarding good faith, particularly in addressing practices such as virtual non-attendance, passive participation, the misuse of technical difficulties, and delaying tactics. Therefore, a more progressive normative interpretation and more detailed technical regulations are needed so that electronic mediation is not merely formal, but effective, fair, and conducted with integrity in dispute resolution in the digital age